Properties of recycled metal matrix composites - Afdzaluddin, Atiqah; Ismail, N; K, K. Lim; Jalar, A; Bakar, M.A.; Maleque, Md. Abdul; Ilyas, R.A.; Supian, A.B.M. (CRC Press, Tailor and Francis Group, 2022)
The utilization of recycled material has been trending for the unconcerned effective consumptions of ecosystems and environmental pollution prevention. In this chapter, the properties of recycling metal matrix composites consisting of physical, mechanical and thermal properties have been briefly explained.